The effects of handling on mouse behavior: cupped hands versus familiar or novel huts or tunnels - Maya J. Bodnar; I. Joanna Makowska; Catherine A. Schuppli; Daniel M. Weary (PLoS ONE, 2025)
Mice are commonly tail-handled, despite evidence that this is aversive. Alternatives include cupping and tunnel handling; both methods are associated with improved welfare outcomes, including reduced anxiety and improved ease of handling, but tail handling may be perceived as more practical for handlers. Practicality may be improved by using handling objects already present in facilities, such as upturned mouse huts. Our first aim was to compare hut handling with the established refined alternatives of cupping and tunnel handling. As both tunnels and huts may be used as part of mouse caging, a second aim was to assess the effects of handling object familiarity (from the home cage vs. a novel object). Outcomes assessed were voluntary interaction with the handler and time spent in the open arms of an elevated plus maze (EPM). Mice (n = 51) were randomly assigned a handling method: cupping, tunnel, or hut. Cages (n = 14) were randomly assigned to contain either a tunnel or hut. Mice underwent 9 days of handling and voluntary interaction tests were conducted on days 1, 5, and 9. On day 10, mice were tested in the EPM. We found that interaction varied with handling object: hut-handled mice spent the most time interacting, followed by tunnel-handled and cupped mice (41.7 ± 1.5 s, 36.1 ± 1.4 s, and 33.0 ± 1.5 s, respectively). Familiar objects improved interaction at the outset, but this difference was no longer evident by day 5. We found no effect of handling object or object familiarity on time spent in the open arms of the EPM. These results suggest that hut handling is a refined handling method; this method may be a practical alternative in facilities that already use huts.